2016
DOI: 10.5194/acp-16-703-2016
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and reactivity of HNCO in water: insights into HNCO's fate in the atmosphere

Abstract: Abstract.A growing number of ambient measurements of isocyanic acid (HNCO) are being made, yet little is known about its fate in the atmosphere. To better understand HNCO's loss processes and particularly its atmospheric partitioning behaviour, we measure its effective Henry's Law coefficient K eff H with a bubbler experiment using chemical ionization mass spectrometry as the gas phase analytical technique. By conducting experiments at different pH values and temperature, a Henry's Law coefficient K H of 26 ± … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 38 publications
7
54
0
Order By: Relevance
“…6 which expresses calculated values for the ozone deposition velocity to carpet as a function of both the uptake coefficient and the velocity of air at the surface (u*). 167 Conversely, 160,[162][163][164][165][166] The locations of the acidic and basic chemicals change in (b) and (c) from (a) due to different assumed polar phase pH values. The same model has been applied to understand observations of gas-surface partitioning in a house.…”
Section: (C) Multiphase Reactionsmentioning
confidence: 99%
“…6 which expresses calculated values for the ozone deposition velocity to carpet as a function of both the uptake coefficient and the velocity of air at the surface (u*). 167 Conversely, 160,[162][163][164][165][166] The locations of the acidic and basic chemicals change in (b) and (c) from (a) due to different assumed polar phase pH values. The same model has been applied to understand observations of gas-surface partitioning in a house.…”
Section: (C) Multiphase Reactionsmentioning
confidence: 99%
“…The lower HNCO mixing ratios in the winter could be due to a reduction in photochemical activity and/or source strength of secondary HNCO precursors (e.g., bio-genic amines) (Woodward-Massey et al, 2014;Roberts et al, 2014), or due to decreased influence from biomass burning. However, the extent to which wild fires contribute to summertime HNCO concentrations is not well established and may be less significant given HNCO's moderate lifetime (as short as a few hours in clouds, but typically weeks to hundreds of years) (Borduas et al, 2016;Barth et al, 2013;Zhao et al, 2014) and the distant location of major Canadian wildfire events relative to Toronto. Although residential wood burning could also contribute to HNCO across the GTA in the winter, a recent study by Coggon et al (2016) showed that common residential wood fuels (e.g., heartwood and sapwood) have low nitrogen content and thus lower emissions of nitrogen-containing VOCs such as HNCO and HCN.…”
Section: Overview Of Mobile Pollutant Measurementsmentioning
confidence: 99%
“…Early studies on some of the first-generation three-way catalysts yielded very high HCN emission factors, typically under abnormal or malfunctioning operating conditions (Bradow and Stump, 1977;Keirns and Holt, 1978;Cadle et al, 1979;Urban andGarbe, 1979, 1980). The magnitude of the HCN emissions exhibited high car-to-car variability and a strong dependence on operating conditions, as well as the presence and composition of the catalysts.…”
Section: Hcn Emission Factorsmentioning
confidence: 99%
“…Isocyanic acid (HNCO) is another highly toxic, long‐lived gas (lifetime of days to decades; Borduas et al, ) emitted from BB with similar anthropogenic and biogenic sources as HCN. Urban sources of HNCO are attributed to primary activity such as automotive emission (Jathar et al, ), residential heating (BB) (Woodward‐Massey et al, ), and industrial processes, for example, from brick kiln emissions (Sarkar et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These bonfires are lit at roughly the same time during the evening and are designed to have a strong flaming phase that lasts for 1-2 h. After flaming, the fires are not refueled and so there is an extended period of smoldering as the fires are left to die away. The UK Environment Agency Isocyanic acid (HNCO) is another highly toxic, long-lived gas (lifetime of days to decades; Borduas et al, 2016) emitted from BB with similar anthropogenic and biogenic sources as HCN. Urban sources of HNCO are attributed to primary activity such as automotive emission (Jathar et al, 2017), residential heating (BB) (Woodward-Massey et al, 2014), and industrial processes, for example, from brick kiln emissions (Sarkar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%